Removal of Zn(II) by modified Rhizopus arrhizus. Issue 54 (19th November 2016) - Feroze, Nadeem; Kazmi, Mohsin; Iqbal, Muhammad Waqas; Yousaf, Sana; Shahzad, Khurram; Fatima, Hira
Abstract: This study shows the potential of modified Rhizopus arrhizus (MRA) for the removal of Zn(II) in water and to investigate the effect of various parameters such as temperature, initial pH, initial concentration, and co-ions. Additionally, kinetic studies and adsorption isotherms have been studied in order to investigate the mechanism of the biosorption process. The results revealed that biosorption on MRA could substantially remove the Zn(II) in water. The biosorption have been found to be pH dependent. The uptake of Zn(II) on MRA increased with the increase in pH. The effect of initial concentration was studied by varying it from concentration 2 to 100 mg/l. The results indicated that the uptake of Zn(II) increases with the increase in initial concentration. The temperature variation (5–40°C) showed Zn(II) uptake on MRA follows an increasing trend. The process was found to be independent of the presence of co-ions. The kinetics studies showed that the uptake of Zn(II) on MRA follows pseudo-second-order kinetics. Results further revealed that the adsorption of Zn(II) on MRA fitted best on the Freundlich isotherm model ( R 2  = 0.998). Therefore, it is concluded that MRA is an affective biosorbent for the removal of Zn(II) in water.